Application of Mollusc Seashell as Aggregate in Concrete - Uchechi G. Eziefula; David O. Onwuka; Hyginus E. Opara (Novel Perspectives of Engineering Research Vol. 3, 2021)
Recent studies on sustainable construction are focused on recycling waste materials in cement-based products. Large volumes of mollusc seashells are commonly dumped as waste in seashores or landfills, posing health and environmental risks, such as pollution and the breeding of vectors. Waste management of mollusc seashells involves recycling the seashell as a partial or total replacement of natural aggregate in concrete. Shells of cockle, mussel, oyster, periwinkle and scallop shellfishes have been used as replacements for coarse and fine aggregates in concrete. Mollusc seashells contain similar calcium carbonate with limestone-type rocks. Chlorides, sulphates, and deleterious organic matter are present in mollusc seashells, but their contents can be reduced through washing and heating. In this chapter, the treatment, preparation, and characteristics of mollusc seashells, as well as the properties of mollusc seashell concrete, are discussed. In addition, the current status, limitations, and prospects of mollusc seashell in sustainable concrete construction are highlighted. The workability, density, and strength properties of concrete generally decrease with increasing seashell replacement. Up to 20% crushed seashell can be utilised as a partial fine aggregate in concrete without causing adverse effects on the density and strength of concrete. Therefore, mollusc seashells can be used as a secondary aggregate in concrete construction, particularly in localities where significant seashell amounts are available.